What Happens When We Read: Picturing a Reader’s Responsibilities - Laurence Musgrove (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
A graphic representation of reading as a process enables students to respond more fully and responsibly to literature by attending to what they contribute to the act of reading, what the world to the text can offer, what kinds of responses are available to them, and what they can do to make sure they have responded as thoughtfully as possible.